2001
DOI: 10.1111/0022-3816.00080
|View full text |Cite
|
Sign up to set email alerts
|

Incumbent Popularity and Vote Choice in Gubernatorial Elections

Abstract: Studies of gubernatorial elections have found vote choice to be a function of party identification, assessments of economic conditions, and the president's job performance but have not tested for a referendum effect concerning the incumbent governor. This analysis uses state polling data to demonstrate that voters with favorable images of the incumbent governor have a higher probability of voting for the candidate of the incumbent's party. The effect is greater when the incumbent seeks reelection, but it is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…The idea that subnational elections are driven by national forces has served as the guiding principal for both micro-level and macro-level research on subnational elections. Among the most consistent findings of these studies is the influence that the incumbent president's popularity has on gubernatorial elections (Atkeson and Partin 1995;Carsey and Wright 1998;Holbrook-Provow 1987;King 2001;Niemi, Stanley, and Vogel 1995;Pierson 1975;Simon, Ostrom, and Marra 1991;Svoboda 1995). Most scholars of these elections concur with Simon's (1989, 301) conclusion that "the electoral fortunes of gubernatorial candidates are tied to the public standing of the president.…”
Section: Determinants Of Gubernatorial Popularitymentioning
confidence: 85%
See 2 more Smart Citations
“…The idea that subnational elections are driven by national forces has served as the guiding principal for both micro-level and macro-level research on subnational elections. Among the most consistent findings of these studies is the influence that the incumbent president's popularity has on gubernatorial elections (Atkeson and Partin 1995;Carsey and Wright 1998;Holbrook-Provow 1987;King 2001;Niemi, Stanley, and Vogel 1995;Pierson 1975;Simon, Ostrom, and Marra 1991;Svoboda 1995). Most scholars of these elections concur with Simon's (1989, 301) conclusion that "the electoral fortunes of gubernatorial candidates are tied to the public standing of the president.…”
Section: Determinants Of Gubernatorial Popularitymentioning
confidence: 85%
“…Several studies have concluded that while both state and national economic conditions influence gubernatorial election outcomes (Chubb 1988;Niemi, Stanley, and Vogel 1995;Squire and Fastnow 1994;Svoboda 1995) notably for the state referendum thesis, voters' decisions in gubernatorial elections are affected by their perceptions of state economic performance but not their perceptions of national economic performance (Atkeson and Partin 1995;Partin 1995). Even closer to the question of gubernatorial popularity is the finding that voters' decisions are based on their assessments of the incumbent governor rather than their assessments of the president (King 2001). These models of gubernatorial voting and election outcomes usually also control for political predispositions of voters or the statewide constituency in the form of political party identification and, occasionally, ideological identification.…”
Section: Determinants Of Gubernatorial Popularitymentioning
confidence: 99%
See 1 more Smart Citation
“…Approval ratings are important not only because they are a key indication of re-election prospects (King 2001) but also because they expand the executive's ability to set their own policy agenda (Canes-Wrone and De Marchi 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that unfavorable evaluations of one's own candidate, favorable evaluations of the other party's candidate, and negative views about the status of the economy would increase the likelihood of changing one's party choice in the voting booth (for example, Bartle, 2003;Beck, 2002;Fournier et al, 2003;King, 2001;Weisberg, 2002;Wekkin, 1991).…”
Section: Other Relevant Explanations For Changes In Party Choicementioning
confidence: 99%